The Perspective of Historical Sociology : the Individual as Homo-Sociologicus Through Society and History. - Šubrt, Jiří (Emerald Publishing Limited, 2017)
This book provides a comprehensive overview of the themes that make up the field of Historical Sociology. At its centre is the human individual as related to social and historical development. The key question it raises is who or what is responsible for the process of human history: society or the individual?